Niveles de orégano deshidratado (Origanum vulgare L.) en dietas para cerdos en crecimiento sobre los parámetros productivos y de salud - Carranza Mejía, Danna Gabriela (2025)
The purpose of this study was to identify the effect of dehydrated oregano during the growth stage of piglets on two parameters: health and productivity. An experimental study lasting four weeks was carried out on a population of 18 pigs, organized into three experimental units, each consisting of six piglets (T1, T2, T3), under a completely randomized block design. The results showed that, although no significant differences were found in growth performance among the three oregano concentration treatments (1%, 2%, and 3%), visible effects were observed on the animals’ appetite. The oregano supplementation improved feed palatability, enhanced mineral utilization from the daily diet, and helped stimulate the appetite of piglets with feeding difficulties. Overall, the use of dehydrated oregano in growing pigs improved their health parameters, showing no morbidity or mortality. Financial analysis by treatment revealed that T3 (3% oregano) achieved the highest net profit of $138.26 and the best cost-benefit ratio of 1.30, indicating that for every dollar invested, a return of $1.30 was obtained.